DINAMIKA POPULASI MIKROBA BENTUK FILAMEN PADA PROSES ANAEROBIK-AEROBIK UNTUK PENAMBATAN POSPAT DENGAN MIKROBA - I Made Sudiana (Research Center for Biology-Indonesian Institute of Sciences, 1999)
Filamentous bulking is commonly observed in activated sludge treatment plant. The present study is intended to study the dynamic of filamentous organism in enhanced biological phosphorous removal. An anaerobic-aerobic sequential batch reactor was operated at 6 cycles per day with anaerobic phase for 55 minutes, aerobic phase for 135 minutes and settling phase for 60 minutes. Population of filamentous organism were counted and identified.Fluorescence in situ hybridization (FISH) with oligonucleotide probe specific for the alpha, beta, gamma sub class Proteobacteria and gram positive high GC DNA content organism was done to identify in-situ community of filamentous organism in the activated sludge. Them were 4 major filamentous organisms namely Type 021N, 0041, Micmthrix oarvicella and Haliscomenobacter hydrosis, in which type 021N was always dominant. Deterioration of enhanced biological phosphorous removal process was observed when filamentous organism outgrew. Probing technique with oligonucleotide probe revealed that filamentous organism mostly belong to the gamma sub class of Proteobacteria.